2018
DOI: 10.1111/geb.12766
|View full text |Cite
|
Sign up to set email alerts
|

Congruence across taxa and spatial scales: Are we asking too much of species data?

Abstract: Aim Biodiversity monitoring and conservation are extremely complex, and surrogate taxa may represent proxies to test methods and solutions. However, cross‐taxon correlations in species diversity (i.e., cross‐taxon congruence) may vary widely with spatial scale. Our goal is to assess how cross‐taxon congruence varies with spatial scale in European temperate forests. We expect that congruence in species diversity increases when shifting from fine to coarse spatial scales, with differences between species richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Consideration to multiple scales is therefore necessary for disentangling difference in the relative contribution of large and small-scale processes across taxa (Burrascano et al, 2018). Lastly, we used different environmental variables as proxies for testing different plausible driving mechanisms for the observed cross-taxon congruence patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consideration to multiple scales is therefore necessary for disentangling difference in the relative contribution of large and small-scale processes across taxa (Burrascano et al, 2018). Lastly, we used different environmental variables as proxies for testing different plausible driving mechanisms for the observed cross-taxon congruence patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, energy and environmentally-related factors still can play an important role in driving patterns of diversity at broad geographic scales (Hawkins et al, 2003). microclimatic conditions, occurrence of specific elements), the inclusion of a wider extent and, consequentially, broader ecological gradients, increased congruence for all pairs of taxa (Burrascano et al, 2018). A recent study on forest communities found that when compared with the effect of fine-scale determinants directly or indirectly related to forest structure (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi‐taxonomic data were collected in six different projects (Burrascano et al, ) using comparable, but not identical sampling protocols (Supporting Information Table S3 for details). All vascular plant species were recorded in plots ranging from 314 to 1,256 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, dynamics in more impacted habitats (e.g., in agroecosystems) or dynamics of mobile organisms (e.g., spore dispersing fungi) could be less sensitive to biogeographical processes being more prone to homogenization (Winter et al, ). This claims for further large scale, multi‐habitat, and multi‐taxon studies and for a habitat and taxon‐specific approach to conservation (Burrascano et al, ; Flensted et al, ; Nascimbene et al, ). According to these findings, EU conservation policies should distinguish between habitat and taxa that are manageable according to a biogeographical approach (McIntosh & Burbidge, ) and those that are more influenced by local processes.…”
Section: Discussionmentioning
confidence: 99%